FRP Composite in Mitigating Seismic Risk of RC Structures in Near-Fault Regions with/without Aftershocks - Vui Van Cao; Son Quang Pham (Advances in Civil Engineering)
The literature related to earthquakes and fibre reinforced polymer (FRP) retrofitting can be divided into two main categories: (1) the applications of FRP to retrofit structures subjected to single traditional earthquakes and (2) the effects of mainshock-aftershock sequences on original structures (without FRP retrofitting). Research on using FRP to mitigate the risk of pulse-type mainshock-aftershock sequences for reinforced concrete (RC) structures located in near-fault regions is hardly found in the literature and is thus the aim of this study. To achieve this aim, a four-storey RC frame, near-fault mainshocks, and seismic sequences were selected. The frame was retrofitted using FRP wraps at plastic hinge locations. Nonlinear time history and damage analyses of the original and FRP-retrofitted frames subjected to these near-fault mainshocks and seismic sequences were conducted. The results showed that aftershocks significantly increase the damage indices of the frames, shifting the damage state of the original frame from severe damage to collapse and the damage state of the FRP-retrofitted frame from light damage to moderate damage. FRP retrofitting successfully reduced the risk of seismic sequences by reducing the damage two levels, shifting the damage state of the original frame from collapse to moderate damage.